The Paris Peace Conference, 1919 - Dockrill, M. author. aut Link
XIV, 197 p.
Keywords: The essays in this volume, written by leading historians and a former British foreign secretary, survey the strategy, politics and personalities of British peacemaking in 1919. Many of the intractable problems faced by negotiators are studied in this volume. Neglected issues, including nascent British commercial interests in Central Europe and attitudes towards Russia are covered, along with important reassessments of the viability of the Versailles treaty, reparations, appeasement, and the long-term effects of the settlement. This collection is a compelling and resonant addition to revisionist studies of the 'Peace to End Peace' and essential reading for those interested in international history.